2008
DOI: 10.1016/j.febslet.2008.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the fnx1+ and fnx2+ genes for vacuolar amino acid transporters in Schizosaccharomyces pombe

Abstract: We have identified the Schizosaccharomyces pombe SPBC3E7.06c gene (fnx2 + ) from a homology search with the fnx1 + gene involving in G 0 arrest upon nitrogen starvation. Green fluorescent protein-fused Fnx1p and Fnx2p localized exclusively to the vacuolar membrane. Uptake of histidine or isoleucine by S. pombe cells was inhibited by concanamycin A, a specific inhibitor of the vacuolar H + -ATPase. Amino acid uptake was also defective in the vacuolar ATPase mutant, suggesting that vacuolar compartmentalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 28 publications
5
31
0
Order By: Relevance
“…We recently reported that the fission yeast fnx1 + and fnx2 + genes, which are homologous to the budding yeast VBA (vacuolar transporter for basic amino acids) genes, are involved in vacuolar amino acid uptake in Sch. pombe (Chardwiriyapreecha et al, 2008). We tested sporulation of fnx1D and fnx2D cells, and found that they sporulate normally during nitrogen starvation (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that the fission yeast fnx1 + and fnx2 + genes, which are homologous to the budding yeast VBA (vacuolar transporter for basic amino acids) genes, are involved in vacuolar amino acid uptake in Sch. pombe (Chardwiriyapreecha et al, 2008). We tested sporulation of fnx1D and fnx2D cells, and found that they sporulate normally during nitrogen starvation (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…After 15 min, 0.5 ml aliquots were withdrawn, filtered on cellulose acetate membrane filters (0.45 mm; ADVANTEC) and washed with cold 10 mM HEPES (pH 6.4). Radioactivity was measured using a liquid scintillation counter with xylene scintillator (Chardwiriyapreecha et al, 2008).…”
Section: The Gga22mentioning
confidence: 99%
“…Amino acid uptake by intact yeast cells involves active transport into vacuoles. 12,15,16) Therefore, it is possible that the uptake activity of amino acids into vacuoles is critical for an increase in the cytosolic concentration. The primary step for the maintenance of intracellular amino acid concentration is a transport across the cell membrane.…”
mentioning
confidence: 99%